Evaluation of the Opportunities for Sustainability Education Through Content-Based Learning in Online German Classes in Ecuador - Schneider, Kathrin (European Journal of Sustainable Development, 2017)
This paper proposes to reflect on online German class as vehicle for sustainability education and evaluates the (up to now unused) opportunities language classes offer. In the last decades, modern methodology for foreign language acquisition like the communicative approach has become increasingly popular to develop linguistic abilities, focusing on content-based instruction. Standardizing documents like the CEFR (Common European Framework of Reference, 2001) are mainly based on this methodology and define fundamental competences (reading, listening, writing, speaking) and sub-competences e.g. reading a newspaper article, writing a personal letter, hold a formal conversation etc. The contents on the contrary are not defined, which allows language class to have a variety of topics that can be chosen by the teacher/tutor. The selection process of the material is, however, key to the success of the project. Foreign language learning can thus be a vehicle to education of specific topics, and hence suitable for sustainability education. The exemplified units are from a lower level (A2) and a middle level (B2). The proposed concept can be a blueprint for other language classes that decide to include sustainability education. Keywords: sustainability education, CEFR, content-based language learning, competences, German as foreign language